Studies of the Ndh complex and photosystem II from mesophyll and bundle sheath chloroplasts of the C4-type plant Zea mays - Darie, Costel C (Journal of plant physiology, 2006)
In C(4) plants, granal mesophyll (MS) chloroplasts contain higher photosystem (PS) II and lower PS I activity than agranal bundle sheath (BS) chloroplasts. The maize NAD(P)H dehydrogenase or NAD(P)H-plastoquinone oxidoreductase (also named Ndh complex) from MS and BS chloroplasts, contains at least 11 subunits (NdhA-K) and is homologous to NADH dehydrogenase or Complex I from mitochondria and bacteria. The amount of Ndh complex is higher in BS compared with MS chloroplasts. However, there is little information about the interdependence of the PS II and Ndh complex in chlororespiration and linear and cyclic electron transport in C(4) plants. To characterize the expression of the PS II and Ndh complex in maize plastids, we used cytochrome b559 (cyt b559) antibodies and Ndh immunoglobulins (IgG) to analyze the Ndh complex and PS II in both MS and BS chloroplasts from maize leaves by Western blotting and immunolabeling. In Western blot experiments, it was found that the amount of cyt b559 (a marker for PS II) is 7-8 times higher in MS than BS chloroplasts. Conversely, the NdhH, -J, -K and -E content is 2.5-3 times higher in BS than MS chloroplasts. Similar results were obtained in immunolabeling experiments using Ndh IgGs and cyt b559 antibodies in MS and BS chloroplasts. These data suggest that in BS chloroplasts, ATP could be produced mainly by cyclic electron transport around PS I and Ndh complexes. Conversely, the linear electron transport in BS chloroplasts via PS II could have a lower production of ATP. These results also suggest that the contribution of the Ndh complex in the production of ATP in MS chloroplasts is minimal and that instead, this complex could have a chlororespiratory role